How Cultural Competency of Community Health Care Providers Reflects Multicultural Education: A Case Study on Nursing Majors (Medico Legal Update, 2021)
In the current global era, multicultural education is a requisite for those who attain higher education, such asnursing majors working in a community with people from a variety of cultural backgrounds. This study aimedto explore the effect of multicultural education by identifying cultural competency (CC) and multiculturalacceptance (MA) among two groups of students and professionals who majored in nursing.A series of surveys was conducted targeting nursing students and clinical professionals. Out of 189participants, data from 98 participants with experience of multicultural education and 91 participants withoutexperience of multicultural education was analyzed. Independent t-tests, correlation tests, and regressionanalysis were conducted to examine the effect of multicultural education, and to identify the correlationbetween CC and MA and the factors influencing them through the comparison of data from each group. Theresults demonstrated two major points. First, multicultural education was shown to enhance CC and MAof the participants. Second, cultural knowledge and cultural experience were important factors influencingMA.These results can be used to provide educational direction regarding cultural competency and multiculturalacceptance, ultimately leading to provision of better healthcare services in multicultural communities.